A molecular-beam optical Stark study of lines in the (1,0) band of the F4Δ7/2-X4Δ7/2 transition of iron monohydride, FeH - Steimle, T; Chen, J; Harrison, J; Brown, J (American Institute of Physics, 2006)
A supersonic molecular beam of iron monohydride, FeH, has been generated using a laser ablation/chemical reaction scheme and probed at near-natural linewidth resolution by optical Stark spectroscopy utilizing laser-induced fluorescence detection. The observed Stark splitting in Q(3.5) and R(3.5) lines of the F4Δ7/2← X4Δ7/2 (1,0) transition were analyzed to determine values for the magnitudes of the permanent electric dipole moments, |μ|, which were found to be 2.63(3) and 1.29(3) D for the X4Δ (υ=0) and F4Δ (υ=1) states, respectively. A comparison with ab initio theoretical predictions is made. The Λ doubling in the low-J levels of the F4Δ7/2(υ=1) state is also modeled.